2013
DOI: 10.1021/jf402004x
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Polyphenols Alleviate Obesity in Broiler Chickens through the Regulation of Lipid-Metabolism-Related Genes and Transcription Factor Expression

Abstract: The current study investigated the effects of green tea polyphenols (GTPs) on lipid metabolism and its mechanisms using broiler chickens (Gallus gallus domesticus). A total of 36 male chickens (35 days old) had been subjected to an oral administration of GTPs at a dosage of 0, 50 (low), and 100 (high) mg/kg of body weight for 20 days. Our results showed that GTPs significantly decreased the abdominal and subcutaneous fat masses of broilers and reduced the serum triglyceride, total cholesterol, and low-density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
85
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 42 publications
10
85
0
2
Order By: Relevance
“…PPAR-α, as a member of nuclear receptors, is highly expressed in the liver and plays an important role in regulating glucose and lipid metabolism or enhancing the related-gene expression in fatty acid oxidation (Lee et al, 1995;Zhang et al, 2011;Huang et al, 2013). LPL, on the other hand, catalyzes triglycerides from circulating chylomicron and very low-density lipoprotein to generate fatty acids and glycerol for tissue utilization or storage (Zhao et al, 2013).…”
Section: Effect Of Cottonseed Meal Fermented With Yeast On the Lipid-mentioning
confidence: 99%
See 1 more Smart Citation
“…PPAR-α, as a member of nuclear receptors, is highly expressed in the liver and plays an important role in regulating glucose and lipid metabolism or enhancing the related-gene expression in fatty acid oxidation (Lee et al, 1995;Zhang et al, 2011;Huang et al, 2013). LPL, on the other hand, catalyzes triglycerides from circulating chylomicron and very low-density lipoprotein to generate fatty acids and glycerol for tissue utilization or storage (Zhao et al, 2013).…”
Section: Effect Of Cottonseed Meal Fermented With Yeast On the Lipid-mentioning
confidence: 99%
“…Nutritionists have tried to mitigate this problem using nutritional strategies, such as the dietary supplementation of plant extracts and probiotics, and some researchers have demonstrated that this is an efficient means of preventing excessive fat deposition. Huang et al (2013) reported that the dietary supplementation of green tea polyphenols (extracted from tea plants) reduced abdominal and subcutaneous fat deposition in broiler chickens by regulating the expression of key genes related to lipid metabolism. Furthermore, Aluwong et al (2013) showed that the supplementation of a yeast probiotic in broiler feeds significantly decreased abdominal fat weight by 16.67% in the group fed 1.5% and by 28.626% in the group fed 2.0% compared with the controls.…”
Section: Introductionmentioning
confidence: 99%
“…Real-time qPCR was used to verify six LM proteins of differential abundance at the mRNA level by the method of Huang et al (2013) with slight modifications.…”
Section: Validation Of Proteins Of Differential Abundancementioning
confidence: 99%
“…The primer sequences are shown in Table S1. The relative fold-change was calculated by the 2 −ΔΔC T method (Huang et al, 2013).…”
Section: Validation Of Proteins Of Differential Abundancementioning
confidence: 99%
“…In particular, green tea polyphenols (GTPs) have been shown to inhibit adipogenesis and induce apoptosis in mouse 3T3-L1 preadipocytes [17,18] . Similarly, GTPs have been shown to reduce obesity and serum lipid levels in broiler chickens by suppressing fatty acid synthesis and stimulating lipolysis [19] . This study was conducted to examine the effects of different green tea extracts (GTEs) on body and organ weight and expression of key adipogenic transcripts in broiler chickens.…”
Section: Introductionmentioning
confidence: 99%